Attractive prices and euro-rounding effects on inflation - Luc Aucremanne; David Cornille (National Bank of Belgium, 2001)
Approximately 70% of Belgian consumer prices are to be considered as attractive prices, namely psychological prices, fractional prices - i. e. prices which are convenient to pay - and round prices. Conversion of these prices into euro generally leads to prices which are no longer attractive and it is very likely that retailers will round their prices to attractive euro prices. The public fears that rounding will be upward rather than symmetric. This paper simulates in the first instance a worst-case scenario, whereby all attractive BEF prices are systematically rounded up to the nearest attractive euro price. The effect on the consumer price index ranges from 0.54 to 0.72%. Such a scenario is however very unlikely, as factors such as competition on product markets, the currently prevailing demand conditions, the commitments made by organisations representing the enterprise sector and the vigilant attitude of consumers restrain the possibility of rounding up. In order to obtain a more realistic picture, the paper investigates in a second step whether rounding-up effects were found after the major change in VAT rates in April 1992. These effects seem marginal, although it should be acknowledged that it was difficult to isolate rounding effects from regular price changes. Any ex post assessment of the euro changeover will face a similar identification problem.
Keywords: 330; Euro; Inflation; Einzelhandelspreis; Belgien